The Influence of Entrepreneurial Characteristics on Business Success in Micro, Small, and Medium Enterprises with Innovation Creativity as a Mediating Variable - Desi Rahmawati; Eko Santoso (Cita konsultindo, 2024)
This research aims to examine the relationship between entrepreneurial traits and the success of micro, small, and medium-sized businesses via the lens of innovation and creativity, which are seen as mediating variables. The descriptive analysis in this study is quantitative in nature. The data processing for this inquiry is done using Smart PLS SEM (Partial et al. - Structural Equation Modeling) software. Using PLS, we can better understand the connection between variables and the ability to perform analyses in a single test. Indicators of hypothesis testing include the probability value and the t-statistic value. What the study found. Test findings showed that entrepreneurial traits (X) affect company success (Y), confirming the original premise. We may conclude that the second hypothesis is correct. Entrepreneurial traits' effect on originality in new product development (X). Third hypothesis testing was successful, showing that innovative originality (Z) affected company performance (Y). Third hypothesis testing was successful, showing that innovative originality (Z) affected company performance (Y).